If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(4a + 8) = a(x + 1) Reorder the terms: 3x + -1(8 + 4a) = a(x + 1) 3x + (8 * -1 + 4a * -1) = a(x + 1) 3x + (-8 + -4a) = a(x + 1) Reorder the terms: -8 + -4a + 3x = a(x + 1) Reorder the terms: -8 + -4a + 3x = a(1 + x) -8 + -4a + 3x = (1 * a + x * a) -8 + -4a + 3x = (1a + ax) Solving -8 + -4a + 3x = 1a + ax Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -8 + -4a + -1a + 3x = 1a + -1a + ax Combine like terms: -4a + -1a = -5a -8 + -5a + 3x = 1a + -1a + ax Combine like terms: 1a + -1a = 0 -8 + -5a + 3x = 0 + ax -8 + -5a + 3x = ax Add '-1ax' to each side of the equation. -8 + -5a + -1ax + 3x = ax + -1ax Combine like terms: ax + -1ax = 0 -8 + -5a + -1ax + 3x = 0 Add '8' to each side of the equation. -8 + -5a + -1ax + 8 + 3x = 0 + 8 Reorder the terms: -8 + 8 + -5a + -1ax + 3x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -5a + -1ax + 3x = 0 + 8 -5a + -1ax + 3x = 0 + 8 Combine like terms: 0 + 8 = 8 -5a + -1ax + 3x = 8 Add '-3x' to each side of the equation. -5a + -1ax + 3x + -3x = 8 + -3x Combine like terms: 3x + -3x = 0 -5a + -1ax + 0 = 8 + -3x -5a + -1ax = 8 + -3x Reorder the terms: -8 + -5a + -1ax + 3x = 8 + -3x + -8 + 3x Reorder the terms: -8 + -5a + -1ax + 3x = 8 + -8 + -3x + 3x Combine like terms: 8 + -8 = 0 -8 + -5a + -1ax + 3x = 0 + -3x + 3x -8 + -5a + -1ax + 3x = -3x + 3x Combine like terms: -3x + 3x = 0 -8 + -5a + -1ax + 3x = 0 The solution to this equation could not be determined.
| 10b+9-36=2 | | 50=5(4-3x) | | 4y-x=-1 | | X=(4x-4)(4k+1) | | 8x-3=2x+15 | | 7x=17-y | | 3(2r+14)=2(25+4r) | | 28-x=3x-84 | | 7x-4y+6=0 | | -15-5x=9-9x | | 15-5x=9-9x | | 6q+13=12q-2 | | 0.5x+6=0.33333x+7 | | 10-p+7p-8p+1+q= | | (x+.1)(x+4.1)=0 | | 9x+23y=11 | | 4+5x+6y-4x-1y-30=0 | | (4x-7)(5x+3)=0 | | 3(X+4)=60 | | (2x+7)(6x-7)=0 | | -6x+5x=-5 | | 0.5x-16=x-24 | | 4x(x-7)=0 | | -1-n+3=1 | | x(x+3)=0 | | -6+x-4x=6 | | (x+6)(x+18)=0 | | 5X-25=10 | | -2b-6b=-16 | | y=150+0.75y-300+300-50+400 | | 1-2v+6v=-7 | | 2t+11=4t-11 |